The Sports Interest in Students' Extracurricular Activities At SMP Negeri 8 Makassar - Ishak, Muhammad; Amahoru, Nurul Musfira; Hudain, Muh Adnan (Sains Global Institut, Indonesia, 2023)
This study aims to determine how much interest students have in extracurricular sports activities of SMP Negeri 8 Makassar students. This research belongs to the type of survey research. The population of this study was all students of SMP Negeri 8 Makassar with a total research sample of 40 students selected by purposive sampling. The data analysis techniques used are descriptive, data normality, and categorization using the SPSS System Version 16.00 at a significant level of 95% or a0.05. Based on the results of data analysis, this study concluded that the interest in sports in extracurricular students of SMP Negeri 8 Makassar was in the category of Strongly Agree